Preparation and sports performance of multilayer flexible anti stabbing fabric martial arts sports composite conjugate materials - Zhang, Jie; Ding, Huanxiang; Wang, Yanqun (Frontiers in Chemistry, 2023)
Martial arts can promote physical fitness, and various sharp tools can cause harm to the human body during the process of martial arts. Anti puncture clothing has important application potential in martial arts. This article studied the preparation process of multi-layer flexible anti stab fabrics and analyzed the movement performance of the fabric to explore the potential application of anti stab clothing in martial arts. This article selected ultra-high molecular weight polyethylene fibers as raw materials and conducted pre-treatment, including fiber cleaning and drying, laminating the fibers, and laminating them together through needle punching. The laminated fibers were soaked in resin, and the soaked fibers were solidified to form a specific flexible anti stab fabric. This article prepared three types of layered fabrics, namely woven fabrics, non-woven materials, and composite materials of non-woven materials+woven fabrics+non-woven materials. The kinematic properties of the three types of layered fabrics were analyzed. The experimental results showed that when the number of layers was 4, the average breaking tensile forces of woven fabrics, non-woven materials, and composite materials were 3400N, 4600N, and 3860N, respectively, and the average elongation at break were 11.8%, 40.6%, and 17.4%, respectively. The breathability and moisture permeability level of woven fabric was the highest. The composite fabric used can have high breaking strength and low breaking elongation at the same time, meeting the tensile requirements of martial arts sports clothing, but the permeability and moisture permeability of composite fabric need to be improved.